Improving Student’s English Vocabulary Mastery Using The Sing and Play Method in Class 4 MIS Baiturrahman Basilam BL 2022/2023 Academic Year - Desi Triana Ayun Sari; Irgi Ahmad Fahrizi; Donny Adiatmana Ginting (English Lecturers and Teachers Association (ELTA), 2023)
This study was structured with the aim of increasing students' vocabulary mastery, increasing motivation and learning outcomes of English for 4th grade students of MIS Baiturrahman Basilam BL 2022/2023 Academic Year using the Sing and Play method. This type of research is Classroom Action Research (CAR). In this study, researchers applied research in three cycles. Researchers used two data collection techniques, namely: observation and tests. Data is classified in the form of qualitative and quantitative. Qualitative data were obtained from observations while quantitative data were obtained from student learning outcomes. The subjects of this study were 4th grade students at MIS Baiturrahman Elementary School, totaling 16 students. Data were analyzed and presented in tabular form. These results also simultaneously show that the use of the Sing and Play method can improve English vocabulary mastery and learning activity for 4th grade students at MIS Baiturrahman Elementary School. Keywords : Methods, Vocabulary, Sing and Play, Learning Outcomes, Elementary School